Uji Daya Antiinflamasi Ekstrak Etanolik Daun Mengkudu (Morinda Citrifolia (L.)) Terhadap Mencit Putih (Mus Musculus) Jantan Galur Swiss Yang Diinduksi Karagenin - Paulina Maya Octasari; Andreas Napoleon (Journal Clinical Pharmacy and Pharmaceutical Science, 2022)
Inflammation is the body's response to protect it self from chemicals, infectious agents, and damage to body tissues caused by injury. Flavonoid compounds can be used as anti-inflammatory by inhibiting the activity of cyclooxygenase (COX) and lipoxygenase enzymes. The amount of flavonoid content in noni leaves was 15.97 mg QE/g extract. The difference between this study and the previous research conducted by Rifaldy, et al (2019) lies in the test animals, the method of measuring inflammation, and the dose of extract used. This study aims to determine the anti-inflammatory power and dosage of the ethanolic extract of noni (Morinda citrifolia (L.)) leaves. This study is an experimental study, using a completely randomized design with one-way pattern with one treatment factor, namely variations in the dose of Noni Leaf Ethanolic Extract (EEDM), namely 42 mg/20gBW mice, 56 mg/20gBW mice, and 70 mg/20gBW mice. The anti- inflammatory test method uses artificial edema formation with carrageenin. The research data was in the form of percentage of anti-inflammatory power (%DAI), thenstatistically analyzed using SPSS with 95% confidence level. The results of the anti-inflammatory power of EEDM from the smallest to the largest doses produced anti-inflammatory properties, namely 55.30%, 62.28%, and 69.41%, this means that the larger the dose, the higher the percentage of anti-inflammatory power (p<0.05). The percentage of anti-inflammatory power of EEDM at a dose of 70 mg/20gBW mice had an anti-inflammatory effect that was not significantly different from the positive control (p>0.05).